Potential of ant nest extract (Hydnophytum formicarum) for protection of testicular morphometry, epididymal functions, and sperm quality in male rats with alloxan-induced diabetes - Roslizawaty, Roslizawaty; Abrar, Mahdi; Khairan, Khairan; Gholib, Gholib; Siregar, Tongku N.; Syafruddin, Syafruddin; Sutriana, Amalia; Azzahra, Putri; Aini, Hanipah (Narra J, 2024)
Medicinal herbs, such as the ant nest plant (Hydnophytum formicarum), are promising for the management of diabetes mellitus-associated infertility. The aim of this study was to evaluate the biological activity of the ant nest plant and its capacity to mitigate the adverse effects of alloxan-induced diabetes on testicular morphology, epididymal function, and sperm quality in male rats. The tuber of the ant nest plant was extracted using methanol and then subjected to phytochemical screenings. For the experiment, 20 male white rats (Rattus norvegicus), aged 3–4 months and weighing 150–200 g, were equally divided into four groups. The ant nest extract was administered orally using oral gavage over 14 days. The testes, epididymis, and sperm were collected for weighing, morphometric measurements, and quality evaluation. Qualitative testing of phytochemical compounds indicated the presence of flavonoids, tannins, steroids, terpenoids, and phenolic compounds in the plants. The results revealed the protective effects of ant nest extract against the adverse fertility effects induced by alloxan and a high-fat diet, as observed in testicular weight (p=0.045), epididymal weight (p=0.041), and sperm quality (p>0.05).